Combined reversible switching of ECD and quenching of CPL with chiral fluorescent macrocycles. Issue 35 (15th August 2018) - Homberg, Alexandre; Brun, Elodie; Zinna, Francesco; Pascal, Simon; Górecki, Marcin; Monnier, Luc; Besnard, Céline; Pescitelli, Gennaro; Di Bari, Lorenzo; Lacour, Jérôme
Abstract : A series of chiral fluorescent macrocycles display a remarkable combination of both +/– ECD and strong on/off CPL reversible switching upon cation binding and displacement. Abstract : Straightforward synthesis and resolution of a series of chiral fluorescent macrocycles are presented, together with their electronic circular dichroism (ECD), strong excimer fluorescence (EF, λ 300 to 650 nm) and allied highly circularly polarized luminescence (CPL, g lum up to 1.7 × 10 −2 ). The ECD, EF and CPL responses are strongly affected by the presence of metal ions (Na +, Ba 2+ ) thanks to deep conformational changes. While ECD signals can be almost completely reversibly inverted upon the complexation/decomplexation of metal ions in a typical binary response, CPL signals are reversibly quenched concomitantly. The designed macrocycles display thus a remarkable combination of both +/− ECD and on/off CPL reversible switching.